DAMPAK KEBIJAKAN KOLONIAL DI JAWA - Yuliati Yuliati (Jurnal Sejarah dan Budaya, 2013)
Abstract. In Indonesia history, colonial policy in 19th century was main cause destruction of traditional economic and politic. The Java traditional life with traditional ties was replaced by legal rational ties. Decline of traditional rulers and more intensive European influence until village level had changed map of social-economic relation. Two phenomena will be sough so that known its impacts. This essay will reveal Java situation in 19th century and its impacts as a result of European penetration.